Blood Ties Religion, Violence, and the Politics of Nationhood in Ottoman Macedonia, 1878-1908 - Yosmaoglu, Ipek (Cornell University Press, 2013)
The region that is today the Republic of Macedonia was long the heart of the Ottoman Empire in Europe. It was home to a complex mix of peoples and faiths who had for hundreds of years lived together in relative peace. To be sure, these people were no strangers to coercive violence and various forms of depredations visited upon them by bandits and state agents. In the final decades of the nineteenth century and throughout the twentieth century, however, the region was periodically racked by bitter conflict that was qualitatively different from previous outbreaks of violence. In Blood Ties, İpek K. Yosmaoğlu explains the origins of this shift from sporadic to systemic and pervasive violence through a social history of the "Macedonian Question."